CAN AXILLARY ULTRASONOGRAPHY WITH CORE NEEDLE BIOPSY BE A USEFUL TOOL IN THE APPROACH OF BREAST CANCER PATIENTS? - Cruz, Marcelo Ribeiro da Luz; Cruz, Valeria Fernandes Roppa; Cunha, Alfredo Almeida; Bravo, Renato Souza (Mastology, 2021)
Introduction: Metastatic involvement of axillary lymph nodes in patients with breast cancer is an important prognostic factor and it also has therapeutic implications. Nevertheless, the use of ultrasound for evaluating axillary lymph node sta-tus has been questioned. Objective: Evaluate the performance of ultrasound with core needle biopsy in the diagnosis of axillary metastasis. Patients and Method: A diagnostic validation study was performed to compare axillary ultrasound with core biopsy versus the surgical procedure. The scenario was a quaternary hospital in Rio de Janeiro where breast cancer patients were treated. The surgical procedure was the gold standard. Performance was assessed by calculating sensitivity, specificity, positive predictive value, negative predictive value, and estimated nodal disease burden. Result:Specificity and positive predictive values were 100% for the presence of axillary metastasis. The false negative rate was only 1.69% with a negative predictive value of 98.31% for the involvement of three or more lymph nodes. Conclusion: Axillary ultrasound with core needle biopsy shows excellent performance in assessing axillary metastatic impairment in patients with breast cancer, proving to be an effective tool in different clinical contexts